Pengembangan Modul Digital Interaktif dalam Pembelajaran Statistika Terapan menggunakan Learning Management System Berbasis Moodle di Masa Pandemi Covid 19 - Rizal Bakri (Indonesian Journal of Learning Education and Counseling, 2021)
This study aims to develop an interactive digital module using Learning Management System (LMS) application with moodle during the Covid-19 pandemic. The research method used in this research is research and development (R&D) with the ADDIE development model that consists of five stages, namely Analyze, Design, Development, Implementation, and Evaluation. The results of this study show that interactive digital modules for applied statistics courses are suitable for use as learning media during the Covid-19 pandemic based on validation results by learning media experts, material experts, lecturers, and students.